SOUTH NATUNA BASIN RECONFIGURATION BASED ON RECENT SEISMIC AND GRAVITY SURVEYS - Tatang Padmawidjaja; Yusuf Iskandar; Andy Setyo Wibowo; Eko Budi Lelono (Scientific Contributions Oil and Gas, 2019)
The Geological Survey Center has conducted a seismic survey in the southern Natuna Sea region to obtain geological information below relating to the potential energy resources of the area. The area research is located in the western part and outside the Singkawang Basin area (BG, 2008), which is separated by a Metamorf ridge. 2D seismic survey results show 3 different rock units, namely shallow marine sedimentary rocks, tertiary sedimentary rocks and pre-Tertiary sedimentary rocks, with pre-Tertiary sediment depths of less than 2000 ms. Interpretation of seismic data shows the pattern of graben structures that form sub-basins. strong refl ectors seen in seismic record can distinguish pre-rift, syn-rift and post-rift deposits. There are 2 wells, namely Datuk 1X and Ambu 1X. Datuk 1X has a depth of 1187 meters, and The Ambu 1X has a depth of 880 meters that is crossed by a seismic line. Both drilling has obtained Tertiary aged sandstone that covers pre-Tertiary bedrock.Gravity anomaly data in the seismic region shows anomaly values between 10 to 54 mgal which form the anomaly ridge and basinThe ridge anomaly extends as an anticline, while the anomaly basin also rises to form a syncline. Sincline and anticline trending southwest - southeast, with widening and narrowing patterns.Based on its geological model, the depth of the sediment is relatively shallow between 1500 to 2000 meters. While the integration between seismic, gravity and geomagnetic data shows the discovery of new basins that have never been described before.Finally, the integration of seismic and gravity data succeed discovers a new basin which has never been delineated before. In addition, it shows the continuity of the regional geological structure spanning from the studied area to the West Natuna Basin which is well known to be rich in hydrocarbon potential.